The impact of research and innovation results on the development of agriculture in the Republic of Moldova - Boris Gaina; Svetlana Fedorchukova; Galina Kobirman (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The results of the activity of the research/development sphere in the Republic of Moldova play an important role in dynamism of the sustainable development of the basic branches of the national economy: agriculture and the food industry. They contribute essentially to providing the country with agricultural raw materials and industrial processing products, sufficient for the needs of the domestic market and for export. Food security and food safety are closely related to the results of technological transfer of research and innovation results in the fields of agro biology and the food industry. The innovative cluster in these sectors of the economy of the Republic of Moldova consists of 9 biological institutes, 6 agricultural institutes and the State Agricultural University of Moldova. The present study also includes some issues of the impact of climate change and the decline of biodiversity, other challenges and risks to the development of agriculture and related branches of the country's economy.
Keywords: Q00; 330; agricultural science; food security; innovation cluster; agro biology